2015
DOI: 10.1590/0103-9016-2014-0267
|View full text |Cite
|
Sign up to set email alerts
|

Crop loading studies on ‘Caricia’ and ‘Eva’ apples grown in a mild winter area

Abstract: ABSTRACT:The crop load level of an apple (Malus × domestica Borkh.) tree impacts fruit yield and quality parameters, tree vigor and biennial bearing. The optimal crop load is that which allows for consistent annual cropping and fruit quality acceptable to the market. We evaluated the effect of crop load on yield and fruit quality of two low-chill apples cv. 'Caricia' and 'Eva', growing in a mild winter area. During 2010 and 2011 crop load was manually adjusted from 2 or 3 to 17 fruits cm −2 of trunk cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 22 publications
2
7
0
Order By: Relevance
“…The present study showed that the Medium and Low-crop load treatments significantly improved the fruit quality (Table 3 ). These results are similar to those previously observed 17 , 50 , showing improved apple quality in terms of each fruit weight, size, and firmness with a decrease in crop load of each tree 10 , 17 , 51 . The significant increase in the rate of good quality fruit resulted in overall economic benefits.…”
Section: Discussionsupporting
confidence: 92%
“…The present study showed that the Medium and Low-crop load treatments significantly improved the fruit quality (Table 3 ). These results are similar to those previously observed 17 , 50 , showing improved apple quality in terms of each fruit weight, size, and firmness with a decrease in crop load of each tree 10 , 17 , 51 . The significant increase in the rate of good quality fruit resulted in overall economic benefits.…”
Section: Discussionsupporting
confidence: 92%
“…The radius r s of the apple models described in Figure 1a,b was set at 35 mm, in agreement with the mean value measured in our laboratory for three apple varieties (Royal Gala, Golden Delicious and Granny Smith), but also with data reported by others [40,45].…”
Section: Monte Carlo Input Datasupporting
confidence: 85%
“…edu). Early fruit production before the trees have developed a complete canopy can permanently limit the final tree size and consequently, can impact future productivity (Castro et al, 2015). Crop load management is particularly important for 'Honeycrisp' because it can limit inconsistent annual flowering and fruit set (Embree et al, 2007), improve fruit quality (Baugher and Schupp, 2010), and decrease susceptibility to storage disorders (Robinson and Watkins, 2009).…”
mentioning
confidence: 99%